EP1106 Evaluation of a late gastrointestinal effects of radiotherapy clinical nurse specialist attending a gynaecological oncology follow-up clinic. (1st November 2019) - Malik, N; Hanna, L; Harris, L; Hudson, E; Burton, S; Maurice, M; Green, J; Turner, J; Ludlow, H
Abstract : Introduction/Background: Patients who receive pelvic radiotherapy may develop gastrointestinal (GI) symptoms which impact on their quality of life (QoL). A GI Specialist Nurse (CNS) has attended our gynaecological follow up clinic since January 2018. This is a new service in addition to a Late GI Effects Clinic based in the local Gastroenterology Department. Methodology: From January 2018 to March 2019, 185 patients had received pelvic radiotherapy. 35% (65) of patients with GI symptoms were identified using the ALERT-B (Taylor et al 2016), a quick and simple screening tool. Those who answered yes to any question were seen by the GI CNS and investigated using the 'Guidance: The Practical Management of Gastrointestinal Symptoms of Pelvic Radiation Disease' (Andreyev et al 2014). Results: Some of the 65 patients had also previously been investigated in the main Late Effects Clinic. The most common findings are shown in table 1 below. Many patients reported more than one symptom. Table 2 below shows the most common abnormal investigation results It was also identified that 22% (14) of patients required specialist dietary advice including certain carbohydrate avoidance, low fat and/or a low FODMAP diet. Conclusion: Late GI effects are not uncommon following pelvic radiotherapy and can have a significant impact on the patients QoL. A GI Late Effects CNS in a gynaeoncology follow-up clinic quickly identifies, investigates and treats affected patients thus avoiding further clinic referral and speeding up the patients recovery. Disclosure: Nothing to disclose